CONVERGENCE VERS DES PRATIQUES DE BONNE GOUVERNANCE. CONSTATS THÉORIQUES ET EMPIRIQUES CAS DES SOCIÉTÉS MAROCAINES COTÉES - Mohammed Terchoune; Soufiane Bouchikhi (European Scientific Journal, ESJ, 2015)
Convergence toward the corporate Governance principles: theoretical and empirical findings-Evidence from Moroccan listed companies. The main purpose of this present paper is to give a synthesis about the convergence toward the corporate Governance practices of the Moroccan listed companies. We tried to present theoretical and empirical studies about the quality of corporate Governance of the Moroccan listed companies. In order, to measure the application of international and national standards of corporate Governance mechanisms, we referred to the Standard§Poor’s scoring of corporate Governance mechanisms practices and also we took an in depth look at the survey conducted in listed companies in 2012, by the IMA. (Institut Marocain des administrateurs).